PEMANFAATAN LAHAN BEKAS PENAMBANGAN BATUBARA UNTUK USAHA BUDIDAYA IKAN YANG BERKELANJUTAN - Henny Pagoray; Ghitarina Ghitarina; Asfie Maidie; Deni Udayana; Ita Zuraida (DINAMIKA PERTANIAN, 2014)
The abandoned land of coal mining activity in a form of pond was used for fish culture by the people of Kutai Kartanegara Regency of East Kalimantan Province. However, the problem occurs firstly when the land opened for the open pit system that should make the change of water quality of physic, chemistry, and biology of pond after mining activity. This research was done to know the existing condition of former coal mining land, and to analyze the sustainability of aquaculture in this area. Aquaculture sustainability in former coal mining ponds were analyzing with multi dimensional scaling which is a developmental method of Rap-fish (rapid appraisal analysis). The results of the analyzing for every dimension showed that ecological, economical, and sociality has approved index, which mean that balanced were occurred in these dimension for sustainability of the aquaculture activity. The ecological dimension, economy, and social in the developing activity must be in balanced without domination to achieve for sustainability.